1972
DOI: 10.1139/v72-291
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation, Physical Properties, and Structure of Oxotetrachloroaquorhenium(VI), ReOCl4(OH2)

Abstract: Oxotetrachloroaquorhenium(VI), ReOC1,-H,O, has been prepared and characterized for the first time by analysis, infrared spectroscopy and single crystal X-ray diffraction. The crystals were orthorhombic, a = 10.834(8), b = 11.089(8), c = 5.51 7(4) A, Pn2,a, Z = 4. Intensity data were recorded by integrating film methods and measured with a Joyce-Loebl microdensitometer, and 624 observable of the 704 measured independent reflections were given non-zero weight in the final cycle of full matrix least-squares refin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1972
1972
2006
2006

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
(9 reference statements)
0
7
0
1
Order By: Relevance
“…O n many occasions. when we thought we had pure samples of crystals, X-ray powder photographs showed that the sample was contaminated with appreciable amounts of "purple frost" (a product which we have not yet characterized), as well as ReOCI,(OH,) and the decomposition products noted previously (2). Because of the difficulty of purifying Rez03C1,(Re03C1),, a legitimate question arises as to whether the measured powder data are for a pure sample.…”
Section: Discussionmentioning
confidence: 93%
“…O n many occasions. when we thought we had pure samples of crystals, X-ray powder photographs showed that the sample was contaminated with appreciable amounts of "purple frost" (a product which we have not yet characterized), as well as ReOCI,(OH,) and the decomposition products noted previously (2). Because of the difficulty of purifying Rez03C1,(Re03C1),, a legitimate question arises as to whether the measured powder data are for a pure sample.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the Re-Cl distances are not quite identical and vary from 2.335 (4) to 2.373 (3)/k, but all interatomic (3) 2.369 (4) Re-CI(4) 2.335 (4) S(1)-C(1) 1.793 (13) S(2)-C(2) 1.809 (14) distances and angles in the [ReC14(H20)O]-complex anion are unexceptional and agree well with values reported for other monooxo complexes of rhenium(V) (see Table 3). A comparison of the bond-distance and bond-angle values in the trans-aquatetrachlorooxorhenate(V) ion, [ReCI4(H20)O]-, and the trans-aquatetrachlorooxorhenium(VI) molecule, [ReC14(H20)O] (Frais & Lock, 1972), is informative (see Table 3). Both are distorted octahedra with an oxo O atom and a water molecule in trans positions and vary only in the oxidation state of Re.…”
Section: Rhenate(v)mentioning
confidence: 99%
“…The ability to form a detectable hydrate, in spite of hydrolytic sensitivity, is common to ReO 2 Cl 3 and ReOCl 4 . [12] If the reaction temperature is too high, a large amount of ReOCl 4 is produced as a byproduct, and the adduct ReO 2 Cl 3 ·ReOCl 4 crystallizes. This adduct also contains a {ReO 2 Cl 3 } 2 dimer, in this case with slightly asymmetric chlorine bridges (Figure 3).…”
mentioning
confidence: 99%